2009
DOI: 10.1016/j.joca.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral region tibial plateau chondrocytes respond differently to in vitro dynamic compression

Abstract: Chondrocytes from different regions of the porcine tibial plateau express mRNA for structural proteins at different levels and respond to equivalent in vitro mechanical loading with distinctive changes in gene expression. These regional biological variations appear to be related to the local mechanical environment in the normal joint, and thus may indicate a sensitivity of the joint to conditions that alter joint loading such as anterior cruciate ligament (ACL) injury, meniscectomy, or joint instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 70 publications
2
39
0
Order By: Relevance
“…Articular cartilage was obtained from the 36 stifle joints of healthy 6-8 month juvenile pigs within 4 h of sacrifice; the animals were sacrificed for an unrelated study. This animal model has been used in a previous study of the effect of mechanical loading on chondrocyte gene expression [16]. The joints were opened under aseptic conditions and rinsed periodically with phosphate-buffered saline (pH 7.2, Invitrogen, Carlsbad, CA) during sample harvesting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articular cartilage was obtained from the 36 stifle joints of healthy 6-8 month juvenile pigs within 4 h of sacrifice; the animals were sacrificed for an unrelated study. This animal model has been used in a previous study of the effect of mechanical loading on chondrocyte gene expression [16]. The joints were opened under aseptic conditions and rinsed periodically with phosphate-buffered saline (pH 7.2, Invitrogen, Carlsbad, CA) during sample harvesting.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the support of a kinematic pathway has been based on evidence of regional topological variations in the properties of knee articular cartilage structure that are thought to arise in response to the variation in local mechanical environment [15]. It has been shown that chondrocyte populations in different regions of the tibial plateau (covered by meniscus versus not covered by meniscus) respond differently to equivalent tissue level mechanical loading [16]. Thus alteration in the in vivo functional joint motion may result in subtle shifts in the load distribution at the knee altering the local mechanical environment and exposing chondrocytes to loading patterns they are unaccustomed to thereby contributing to degenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…Without in vivo data or in silico estimates of forces distributed across the articular surface of the pig humeral head, it is difficult to gauge the functional significance of regional variation in cartilage parameters. Interestingly, a recent study demonstrated the presence of regional differences in articular chondrocyte responses to mechanical loading, suggesting the possibility that even under uniform loads different cartilage regions may not respond uniformly (Bevill et al, 2009). As chondrocytes are particularly sensitive to the three-dimensional microenvironment and differentiate in response to local signals (Lemare et al, 1998;Goldring, 2004a;Goldring, 2004b), the expression of cartilage ECM elements likely exhibit regional variation due to subtle differences in loading patterns in distinct joint regions (Bayliss et al, 1983;Nakano and Scott, 1989;Mow et al, 1990;Mizoguchi et al, 1996;Tanaka et al, 2000).…”
Section: P<005 Limb Loading and Joint Plasticitymentioning
confidence: 99%
“…It was recently shown that asymptomatic knees have a characteristic region of thicker cartilage in each of the medial, lateral, and trochlea compartments [20][21][22]. These regions are of primary interest in a first analysis of the cartilage thickness shape because articular cartilage thickness and metabolism have been shown to locally adapt in response to applied loads [2,[23][24][25], knee loading has been reported to change with OA progression [26][27][28][29], and OA-related cartilage lesions have been associated with areas of high mechanical stress [30]. These three regions also agree with typical injury sites and the location of full-thickness lesions in the femoral cartilage [31,32], further supporting their selection for this study.…”
Section: Introductionmentioning
confidence: 99%